2021
DOI: 10.1080/13102818.2021.1938674
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, phylogeny and expression analysis of the bZIP gene family in Alfalfa (Medicago sativa)

Abstract: Among eukaryotic transcription factors, the basic leucine zipper (bZIP) transcription factor is the most widely distributed and the most conserved protein. Alfalfa (Medicago sativa) is the largest forage crop in the world. However, few studies have evaluated the bZIP family in Alfalfa. In this study, bZIP genes in Alfalfa were identified, with 57 MsbZIPs being distributed into 11 sub-families in the phylogenetic tree. Motif and gene structure analysis revealed that the eleven subfamilies had similar motifs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Similarly, the allotetraploid (B) napus genome contained 247 bZIP genes, which is roughly double that of the number found in the related diploid A. thaliana. There has been previous study of bZIP genes in Alfalfa [50], where 57 MsbZIPs were identified. However, given the tetraploid genome of alfalfa and compared with its diploid counterpart, the number of bZIPs in the current study looks comprehensive to the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the allotetraploid (B) napus genome contained 247 bZIP genes, which is roughly double that of the number found in the related diploid A. thaliana. There has been previous study of bZIP genes in Alfalfa [50], where 57 MsbZIPs were identified. However, given the tetraploid genome of alfalfa and compared with its diploid counterpart, the number of bZIPs in the current study looks comprehensive to the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…As the genomic characteristics of plants have been increasingly decoded, a growing number of gene families encoded therein have been identified and characterized. Many bZIP TF family members have been isolated to date across a wide number of plant species, including Arabidopsis [11], alfalfa [17], barley [18], cassava [19], castor bean [20], soybean [21], cucumber [22], grapevine [23], legume [24], maize [25], olive [26], rice [27], and sorghum [28]. These include the abscisic acid (ABA)-responsive element (ABRE) binding factor (ABF) and ABA-responsive element binding protein (AREB) (ABF/AREB) subfamily of bZIP TFs, which are essential regulators of the expression of downstream stress-responsive genes in pathways associated with ABA [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa, the most widely cultivated legume forage in the world with a planting area of 32 million hectares ( Ren et al., 2021 ), is known as the “queen of forage” because of its high nutritional value as a source of proteins, vitamins, and other nutrients for livestock. It also exhibits potential for ethanol production ( Liu et al., 2021 ). Alfalfa is widely cultivated in the arid and semiarid areas of the Northeast, Northwest, and Central North regions of China, and its production is strongly constrained by various biotic and abiotic stresses ( Dong et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%